Incineration of waste at Casey Station, Australian Antarctic Territory - JS O'Brien; John Todd; LK Kriwoken (2004)
The Australian Antarctic Division manages four permanent stations in the sub-Antarctic and Antarctic. At each station a municipal waste incinerator is used to dispose of putrescible waste, wood, paper, cardboard, and plastics. Incineration significantly reduces the volume of waste but this combustion also emits toxic compounds. This study examined the waste incineration stream at Casey Station, Australian Antarctic Territory. The waste stream was sorted, burnt, and the incinerator emissions monitored. Twelve chemical compounds in gaseous emissions and heavy metals in the ash were measured. Results indicate that emissions of carbon monoxide are higher than one might expect from a small incinerator, and hydrocarbon emissions from the incinerator exceed combined hydrocarbon emissions from other sources on station. Arsenic and copper concentrations in ash, which is returned to Australia for disposal, exceed limits for hazardous waste disposal and so treatment would be required. Recommendations are provided on controlling source material in order to reduce or eliminate toxic emissions and undertaking incinerator maintenance to optimise combustion.